Effects of irrigation solutions and Calcium hydroxide dressing on root canal treatments of periapical lesions - Vita Nirmala (Dental Journal (Majalah Kedokteran Gigi), 2006)
The preparation of root canal in endodontic treatment plays an important role in treating non vital teeth with periapical lesion. Some factors influence the success of root canal treatment in short and long terms are the irrigation of root canal using antiseptic solution and the use of root canal medicament. The aim of this literature study is to determined the effect of irrigation solution and Calcium hydroxide dressing in root canal treatment of periapical lesions. The use of root canal medicament during the endodontic treatment could sterilized and decreased the number of pathogenic microorganism of root canal. An effective root canal irrigation solution must be able to dissolve organic and anorganic debris, lubricate endodontic instruments, disinfect microorganisms, non toxic and economical. The best irrigation solution has maximum antimicrobial effect with minimum toxicity. Division of calcium hydroxide into Calcium and hydroxyl ions is responsible for alkalinization of cavity, subsequently it makes the condition of cavity to be inappropriate for bacterial endotoxin in vitro as well as in vivo, and considered as the only clinically effective medicament in inactivating bacterial endotoxin. Calcium hydroxide is the only medication which has the ability to clinically inactive bacterial endotoxin in vitro in vivo and accepted as the best of root canal medication.